2013
DOI: 10.1002/ptr.4971
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐Gallate Inhibits Collagen Production of Nasal Polyp‐Derived Fibroblasts

Abstract: Nasal polyps are chronic inflammatory conditions characterized by myofibroblast differentiation and extracelluar matrix accumulation. The major catechin from green tea is (-)-epigallocatechin-3-gallate (EGCG), which has garnered attention for its potential to prevent oxidative stress-related diseases. The purpose of this study was twofold: (i) to determine the effect of EGCG on fibroblast differentiation into myofibroblasts and extracellular matrix accumulation in transforming growth factor (TGF)-β1-induced na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Our laboratory and others have found that EGCG and luteolin are capable of preventing development and/or maintenance of myofibroblast phenotypes when used at relatively high micromolar concentrations. Our most effective dose of EGCG was similar to that found by Kang et al who showed that approximately 20–40 µM EGCG inhibited α-SMA and collagen type I production in nasal polyp-derived fibroblasts [50] and to another study which found that 40 µM EGCG largely obliterated fibronectin production in primary dermal fibroblasts [51] . However, these concentrations are likely to have off-target effects, causing deleterious toxicity in vivo and likely represent concentrations that cannot be achieved in vivo .…”
Section: Discussionsupporting
confidence: 88%
“…Our laboratory and others have found that EGCG and luteolin are capable of preventing development and/or maintenance of myofibroblast phenotypes when used at relatively high micromolar concentrations. Our most effective dose of EGCG was similar to that found by Kang et al who showed that approximately 20–40 µM EGCG inhibited α-SMA and collagen type I production in nasal polyp-derived fibroblasts [50] and to another study which found that 40 µM EGCG largely obliterated fibronectin production in primary dermal fibroblasts [51] . However, these concentrations are likely to have off-target effects, causing deleterious toxicity in vivo and likely represent concentrations that cannot be achieved in vivo .…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that TGF-β1 promotes mRNA expression of type I collagen in fibroblasts [19,20], stimulates the proliferation of cardiac fibroblasts and collagen synthesis [21]. Myocardial fibrosis is characterized by myocardial stromal remodeling; hyperglycemia, oxidative stress and excessive accumulation of ROS may be important factors in the formation and development of myocardial fibrosis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that maple syrup might affect the expression or activation of enzymes, such as MMP-2 and MMP-9, which play an important role in cell invasion of the extracellular matrix, including the basement membrane. Although there is no report on the effect of maple syrup on cell invasion, a recent study reported that polyphenols such as epigallocatechin-3-gallate inhibit MMP-2 and MMP-9 expression ( 24 28 ). Therefore, the expression levels of MMP-2 and MMP-9 in CRC cells might be inhibited by polyphenols such as quebecol and ginnalins that are present in maple syrup.…”
Section: Discussionmentioning
confidence: 99%